Characteristics of Bonggolan Made from the Proportion of Pacific Tarpon (Megalops cyprinoides): Millet Flour (Setaria italica): Tapioca Flour and Carrageenan Addition - Nurlaily, Rizka; Rosida; Yunita Satya Pratiwi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Bonggolan is a typical food from Sidayu, Gresik Regency with chewy texture, savory taste and distinctive fish aroma. In this study, the process of making bonggolan from pacific tarpon meat using millet flour and tapioca flour, and the addition of carrageenan was studied. The purpose of this study was to determine the effect of the proportion of fish meat: millet flour: tapioca flour and the addition of carrageenan on the physicochemical and organoleptic characteristics of bonggolan, and to determine the best treatment combination of these treatments. This study used Completely Randomized Design (CRD) factorial pattern with two factors and three replications. The first factor was the proportion of fish meat: millet flour: tapioca flour (40:10:50, 30:20:50, 20:30:50). The second factor was the addition of carrageenan (1.0%, 1.5%, 2.0%). Data were analyzed using ANOVA at 5% level. If there was a significant difference, a further test was carried out at 5% DMRT. The results of the study showed that the proportion of fish meat: millet flour: tapioca flour (40:10:50) and the addition of carrageenan (2.0%) was the best treatment. In this treatment, the water content was 58.82%, ash content 3.28%, protein content 19.59%, fat content 4.45%, crude fiber content 3.55%, hardness 2133.35 g, springiness 0.95, and the level of preference for color parameters 3.80 (neutral), aroma 3.44 (neutral), taste 3.04 (neutral), and texture 3.36 (neutral).